Cryopreservation process alters the expression of genes involved in pathways associated with the fertility of bull spermatozoa - Ebenezer Samuel King, John Peter; Sinha, Manish Kumar; Kumaresan, Arumugam; Nag, Pradeep; Das Gupta, Mohua; Arul Prakash, Mani; Talluri, Thirumala Rao; Datta, Tirtha Kumar (Frontiers in Genetics, 2022)
In bovines, cryopreserved semen is used for artificial insemination; however, the fertility of cryopreserved semen is far lower than that of fresh semen. Although cryopreservation alters sperm phenotypic characteristics, its effect on sperm molecular health is not thoroughly understood. The present study applied next-generation sequencing to investigate the effect of cryopreservation on the sperm transcriptomic composition of bull spermatozoa. While freshly ejaculated bull spermatozoa showed 14,280 transcripts, cryopreserved spermatozoa showed only 12,375 transcripts. Comparative analysis revealed that 241 genes were upregulated, 662 genes were downregulated, and 215 genes showed neutral expression in cryopreserved spermatozoa compared to fresh spermatozoa. Gene ontology analysis indicated that the dysregulated transcripts were involved in nucleic acid binding, transcription-specific activity, and protein kinase binding involving protein autophosphorylation, ventricular septum morphogenesis, and organ development. Moreover, the dysregulated genes in cryopreserved spermatozoa were involved in pathways associated with glycogen metabolism, MAPK signalling, embryonic organ morphogenesis, ectodermal placode formation, and regulation of protein auto-phosphorylation. These findings suggest that the cryopreservation process induced alterations in the abundance of sperm transcripts related to potential fertility-associated functions and pathways, which might partly explain the reduced fertility observed with cryopreserved bull spermatozoa.